SURVEI PENGUKURAN STATUS GIZI BALITA DAN POLA PEMBERIAN MAKANAN PENDAMPING ASI DI RPTRA MANDALA KELURAHAN TOMANG JAKARTA BARAT - Pambudi, Wiyarni; Fransiska Farah,; Santoso, Alexander Halim; Bruce Edbert,; Dea Angelina,; Nurlita Safna Septianti, (Jurnal Bakti Masyarakat Indonesia, 2023)
The Environmental Community Service (PKM) activity at RPTRA Mandala, Tomang Village, West Jakarta, was carried out in June 2022 in the form of checking the nutritional status of toddlers and counseling with the aim of increasing public awareness in stunting prevention efforts. Abdimas was followed by mothers and caregivers (grandmothers/aunts) of 123 toddlers living in RW 1-16, Tomang Village. The history of infant feeding showed that 64% were exclusively breastfed, and 86% started complementary feeding at the age of 6 months, with a pattern of 78% eating regularly (3-4 times per day), and 59% consuming snacks irregularly (more than 2 times per day). Anthropometric examination found 56% of children under five with normal BW/U, 67% normal BW/U, and 54% normal BW/TB. Gender of children under five had a significant relationship with BB/TB (p=0.026; PR=1.9) but not significant for BB/U (p=0.065; PR=1.4) and TB/U (p=0.057; PR= 1,2). Exclusive breastfeeding was significantly associated with BW/U (p=0.028; PR=1.9) and BW/TB (p=0.045: PR=1.5), but not significant for TB/U (p=0.081; PR= 4.1). Timely complementary feeding showed a significant relationship with BW/U (p= 0.043; PR=3), TB/U (p<0.001; PR=2.4), and BW/TB (p=0.048; PR=1.6). Giving the main MPASI menu regularly 3-4 times per day had a significant relationship with BW/U (p=0.07; PR=4.2), but not significantly with TB/U (p=0.301; PR=1.7 ) and BB/TB (p=0,203; PR=3,3). The practice of irregular snacks, exceeding the recommendation of 1-2 times per day, showed a significant relationship with body weight (p<0.001; PR=1.1), TB/U (p<0.001; PR=2.1), and BW/TB (p=0.002; PR=2,3). Feeding infants and children is proven to determine the nutritional status of toddlers, special attention needs to be given to improving the practice of snacking for toddlers. ABSTRAK: Kegiatan Pengabdian Kepada Masyarakat (PKM) Lingkungan di RPTRA Mandala, Kelurahan Tomang, Jakarta Barat, dilaksanakan pada bulan Juni 2022 dalam bentuk pemeriksaan status gizi balita dan penyuluhan dengan tujuan peningkatan kesadaran masyarakat dalam upaya pencegahan stunting. Abdimas diikuti oleh ibu dan pengasuh (nenek/bibi) dari 123 balita yang tinggal di RW 1-16 Kelurahan Tomang. Riwayat pemberian makan bayi menunjukkan 64% mendapat ASI eksklusif, dan 86% mulai diberikan MPASI saat usia 6 bulan, dengan pola 78% makan secara teratur (3-4 kali per hari), dan 59% mengonsumsi makanan selingan secara tidak teratur (lebih dari 2 kali per hari). Pemeriksaan antropometri menemukan 56% balita dengan BB/U normal, 67% TB/U normal, dan 54% BB/TB normal. Jenis kelamin balita memiliki hubungan bermakna dengan BB/TB (p=0,026; PR=1,9) namun tidak bermakna untuk BB/U (p=0,065; PR=1,4) dan TB/U (p=0,057; PR=1,2). ASI eksklusif berhubungan secara bermakna dengan BB/U (p=0,028; PR=1,9) dan BB/TB (p=0,045: PR=1,5), namun tidak bermakna untuk TB/U (p=0,081; PR=4,1). MPASI tepat waktu menunjukkan hubungan bermakna dengan BB/U (p= 0,043; PR=3), TB/U (p<0,001; PR=2,4), dan BB/TB (p=0,048; PR=1,6). Pemberian menu MPASI utama yang teratur 3-4 kali per hari memiliki hubungan bermakna dengan BB/U (p=0,07; PR=4,2), namun tidak bermakna dengan TB/U (p=0,301; PR=1,7) dan BB/TB (p=0,203; PR=3,3). Praktik makanan selingan tidak teratur, melebihi rekomendasi 1-2 kali per hari, menunjukkan hubungan bermakna dengan BB/U (p<0,001; PR=1,1), TB/U (p<0,001; PR=2,1), dan BB/TB (p=0,002; PR=2,3). Pemberian makan bayi dan anak menentukan status gizi balita, perhatian khusus perlu diberikan untuk perbaikan praktik makanan selingan untuk balita.